2015
DOI: 10.1371/journal.pone.0123931
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Antigen 2 (BST-2) DNA Is Demethylated in Breast Tumors and Breast Cancer Cells

Abstract: BackgroundBone marrow stromal antigen 2 (BST-2) is a known anti-viral gene that has been recently identified to be overexpressed in many cancers, including breast cancer. BST-2 is critical for the invasiveness of breast cancer cells and the formation of metastasis in vivo. Although the regulation of BST-2 in immune cells is unraveling, it is unknown how BST-2 expression is regulated in breast cancer. We hypothesized that meta-analyses of BST-2 gene expression and BST-2 DNA methylation profiles would illuminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…The spectrum of BST-2 expression in various cancers has been revealed using meta analyses studies of large tumor datasets [119]. In solid tumors, BST-2 expression is elevated in head and neck cancer [120], lung cancer [121], breast cancer [119,122,123], cervical cancer [124], myelomas [125,126], endometrial cancer [127], and glioblastoma [128]. In addition, data from proteinatlas.org reveal that BST-2 is overexpressed in colorectal cancer, ovarian cancer, thyroid cancer, and pancreatic cancer (http://www.proteinatlas.org/ ENSG00000130303-BST2/cancer).…”
Section: Bst-2/tetherin: Roles In Carcinogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…The spectrum of BST-2 expression in various cancers has been revealed using meta analyses studies of large tumor datasets [119]. In solid tumors, BST-2 expression is elevated in head and neck cancer [120], lung cancer [121], breast cancer [119,122,123], cervical cancer [124], myelomas [125,126], endometrial cancer [127], and glioblastoma [128]. In addition, data from proteinatlas.org reveal that BST-2 is overexpressed in colorectal cancer, ovarian cancer, thyroid cancer, and pancreatic cancer (http://www.proteinatlas.org/ ENSG00000130303-BST2/cancer).…”
Section: Bst-2/tetherin: Roles In Carcinogenesismentioning
confidence: 99%
“…The significance of elevated BST-2 in various cancers is beginning to evolve. However, not all cancers have elevated BST-2 [119] (Table 2). Compared to normal tissues, BST-2 expression in lung adenocarcinoma and thyroid cancer is unchanged [119] whereas levels of BST-2 in lung squamous cell carcinoma, kidney papillary cell carcinoma, kidney chromophobe carcinoma, liver, and prostate cancer is significantly downregulated [119].…”
Section: Bst-2/tetherin: Roles In Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…[6,9] , cervical cancer [10] , myeloma, endometrial cancer [11] , etc., suggesting that BST-2 has a carcinogenic effect. This experiment confirmed that …”
Section: Discussionmentioning
confidence: 99%